Cardiotoxicity of the BCR-ABL1 tyrosine kinase inhibitors: Emphasis on ponatinib. (1st October 2020) - Singh, Anand Prakash Anand; Umbarkar, Prachi Prachi; Tousif, Sultan; Lal, Hind
Abstract: The advent of tyrosine kinase inhibitors (TKIs) targeted therapy revolutionized the treatment of chronic myeloid leukemia (CML) patients. However, cardiotoxicity associated with these targeted therapies puts the cancer survivors at higher risk. Ponatinib is a third-generation TKI for the treatment of CML patients having gatekeeper mutation T315I, which is resistant to the first and second generation of TKIs, namely, imatinib, nilotinib, dasatinib, and bosutinib. Multiple unbiased screening from our lab and others have identified ponatinib as most cardiotoxic FDA approved TKI among the entire FDA approved TKI family (total 50+). Indeed, ponatinib is the only treatment option for CML patients with T315I mutation. This review focusses on the cardiovascular risks and mechanism/s associated with CML TKIs with a particular focus on ponatinib cardiotoxicity. We have summarized our recent findings with transgenic zebrafish line harboring BNP luciferase activity to demonstrate the cardiotoxic potential of ponatinib. Additionally, we will review the recent discoveries reported by our and other laboratories that ponatinib primarily exerts its cardiotoxicity via an off-target effect on cardiomyocyte prosurvival signaling pathways, AKT and ERK. Finally, we will shed light on future directions for minimizing the adverse sequelae associated with CML-TKIs. Highlights: Radiation and chemotherapy-induced cardiotoxicity is well established. However, kinase inhibitors (KIs)-induced cardiotoxicity is less recognized. Multiple labs have identified ponatinib as most cardiotoxic FDA approved KI. Ponatinib is the only treatment option for CML patients with T315I mutation. Herein, ponatinib and other CML KIs-induced cardiotoxicity is discussed.